Laminated substrates, laminates for packaging materials, and packaging materials
Patent Information
- Application Number
- JP2018168340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2018-09-07
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2038-09-07
AI Technical Summary
【0018】 本発明によれば、包装材料として十分な強度やバリア性を備え、かつリサイクル性にも優れる包装材料の作製を可能とする、積層基材を提供することができる。
Smart Images

Figure 0007933467000009 
Figure 0007933467000010 
Figure 0007933467000011
Abstract
Description
[Technical Field]
[0001] The present invention relates to a laminated substrate, a laminate for packaging materials comprising the laminated substrate, and a packaging material composed of the laminate. [Background technology]
[0002] Traditionally, resin films made from resin materials have been used as constituent materials for packaging. For example, resin films made from polyolefins are widely used in packaging materials because they have moderate flexibility and transparency, as well as excellent heat-sealing properties.
[0003] Typically, resin films made from polyolefins are inferior in terms of strength and heat resistance, and therefore cannot be used as a base material. Instead, they are used in combination with resin films made from polyester, polyamide, etc. Therefore, typical packaging materials consist of laminated films in which the base material and the heat-seal layer are made of different resin materials (for example, Patent Document 1).
[0004] In recent years, with the growing demand for a circular economy, there has been a need for packaging materials with high recyclability. However, as mentioned above, conventional packaging materials are composed of different types of resin materials, making it difficult to separate them, and therefore they are not currently recycled. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2009-202519 [Overview of the project] [Problems that the invention aims to solve]
[0006] The inventors have found that polyolefins, which were conventionally used as heat-sealing layers, can be used as a base material by forming them into stretched resin films. Furthermore, we have found that by laminating this substrate with a heat-seal layer made of the same polyolefin, it is possible to create a packaging material that has the strength and heat resistance required for packaging, and is also recyclable. Furthermore, the inventors have found that by configuring the substrate with a laminated structure that includes a barrier coating layer on one side, it is possible to create a packaging material with high barrier properties while maintaining recyclability.
[0007] This invention has been made in view of the above findings, and the problem it aims to solve is to provide a laminated substrate that enables the production of a packaging material that has sufficient strength and barrier properties as a packaging material, and is also highly recyclable.
[0008] Furthermore, the problem that the present invention aims to solve is to provide a laminate for packaging materials that includes the laminated substrate.
[0009] Furthermore, the problem that the present invention aims to solve is to provide a packaging material composed of a laminate for packaging materials. [Means for solving the problem]
[0010] The laminated substrate of the present invention comprises a polyolefin resin layer and a barrier coat layer. The polyolefin resin layer is characterized by being a stretched resin film.
[0011] In one embodiment of the present invention, the thickness of the barrier coating layer is smaller than the thickness of the polyolefin resin layer.
[0012] The laminate for packaging materials of the present invention comprises the above-mentioned laminated base material and a heat-seal layer. The heat seal layer is made of polyolefin. The polyolefin constituting the polyolefin resin layer of the laminated base material and the polyolefin constituting the heat seal layer are the same polyolefin.
[0013] In one embodiment of the present invention, the laminate for packaging materials comprises a vapor-deposited film between the laminated base material and the heat seal layer.
[0014] In one embodiment of the present invention, the laminate for packaging materials comprises an adhesive layer between the laminated base material and the vapor-deposited film.
[0015] In one embodiment of the present invention, the vapor-deposited film is an aluminum vapor-deposited film, The adhesive layer includes a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound.
[0016] In one embodiment of the present invention, the content of the polyolefin in the entire laminate for packaging materials is 80% by mass or more.
[0017] The packaging material of the present invention is characterized by being constituted from the above laminate for packaging materials. [Effects of the Invention]
[0018] According to the present invention, it is possible to provide a laminated base material that enables production of a packaging material having sufficient strength and barrier properties as a packaging material and also having excellent recyclability. [Brief Description of the Drawings]
[0019] [Figure 1] It is a schematic cross-sectional view showing one embodiment of the laminate for packaging materials of the present invention. [Figure 2] It is a schematic cross-sectional view showing one embodiment of the laminate for packaging materials of the present invention. [Figure 3] It is a schematic cross-sectional view showing one embodiment of the laminate for packaging materials of the present invention. [Figure 4] It is a schematic cross-sectional view showing one embodiment of the laminate for packaging materials of the present invention. [Figure 5] This is a schematic cross-sectional view showing one embodiment of the laminate for packaging materials of the present invention. [Figure 6] This is a perspective view showing one embodiment of a packaging material made using the laminate for packaging materials of the present invention. [Figure 7] This is a perspective view showing one embodiment of a packaging material made using the laminate for packaging materials of the present invention. [Modes for carrying out the invention]
[0020] (Laminated base material) As shown in Figure 1, the laminated substrate 10 of the present invention comprises a polyolefin resin layer 11 and a barrier coat layer 12, and is characterized in that the polyolefin resin layer is a stretched resin film made of polyolefin.
[0021] In the present invention, it is preferable that the thickness of the barrier coat layer is smaller than the thickness of the polyolefin resin layer. By adopting this configuration, when the laminated substrate of the present invention is used as the substrate for a laminated packaging material, the recyclability of the laminated packaging material can be improved. The thickness of the barrier coat layer is preferably 5 μm or more smaller than the thickness of the polyolefin resin layer, and more preferably 10 μm or more smaller. By making the barrier coat layer 5 μm or more smaller than the thickness of the polyolefin resin layer, the recyclability of the laminate for packaging materials can be further improved.
[0022] (Polyolefin resin layer) The polyolefin resin layer is composed of polyolefins, such as polyethylene, polypropylene, polymethylpentene, ethylene-propylene copolymer, and propylene-butene copolymer, with polyethylene and polypropylene being preferred among these.
[0023] As polyethylene, its density is 0.945 g / cm³. 3 Ultra-high density polyethylene (HDPE), density 0.925~0.945 g / cm³ 3Medium-density polyethylene (MDPE), density 0.925 g / cm³ 3 Examples include low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) with a density of less than 1.5 mm.
[0024] In one embodiment, the polyolefin resin layer can be configured to include a layer made of high-density polyethylene (hereinafter referred to as the high-density polyethylene layer) and a layer made of medium-density polyethylene (hereinafter referred to as the medium-density polyethylene layer). By incorporating a high-density polyethylene layer, the strength and heat resistance of the laminated substrate of the present invention can be improved. Furthermore, by incorporating a medium-density polyethylene layer, the stretchability of the resin film when producing the polyolefin resin layer can be improved.
[0025] For example, it has a structure consisting of a high-density polyethylene layer and a medium-density polyethylene layer. By using such a structure, the stretchability of the resin film when producing the polyolefin resin layer can be improved. Furthermore, the strength and heat resistance of the laminated substrate of the present invention can be improved. When a laminated substrate having a polyolefin resin layer with such a structure is applied to a laminate for packaging materials, the high-density polyethylene layer is located on the outermost surface. In this case, it is preferable that the thickness of the high-density polyethylene layer is thinner than the thickness of the medium-density polyethylene layer. The ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 10 or more, the strength and heat resistance of the laminated substrate of the present invention can be improved. Furthermore, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 1 or less, the stretchability of the resin film when producing the polyolefin resin layer can be improved.
[0026] Furthermore, for example, the structure can consist of a high-density polyethylene layer / medium-density polyethylene layer / high-density polyethylene layer. This configuration improves the stretchability of the resin film when producing the polyolefin resin layer. Furthermore, it improves the strength and heat resistance of the laminated substrate of the present invention. Additionally, it prevents curling in the polyolefin resin layer. In this case, it is preferable that the thickness of the high-density polyethylene layer is thinner than the thickness of the medium-density polyethylene layer. The ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 10 or more, the strength and heat resistance of the laminated substrate of the present invention can be improved. Furthermore, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 1 or less, the stretchability of the resin film when producing the polyolefin resin layer can be improved.
[0027] Furthermore, for example, the structure can consist of a high-density polyethylene layer / medium-density polyethylene layer / low-density polyethylene layer or a linear low-density polyethylene layer / medium-density polyethylene layer / high-density polyethylene layer from the outside in. This configuration improves the stretchability of the resin film when producing the polyolefin resin layer. Furthermore, it improves the strength and heat resistance of the laminated substrate of the present invention. Additionally, it prevents curling. In this case, it is preferable that the thickness of the high-density polyethylene layer is thinner than the thickness of the medium-density polyethylene layer. The ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 10 or more, the strength and heat resistance of the laminated substrate of the present invention can be improved. Furthermore, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 1 or less, the stretchability of the resin film when producing the polyolefin resin layer can be improved. Furthermore, it is preferable that the thickness of the high-density polyethylene layer be thinner than the thickness of the low-density polyethylene layer or the linear low-density polyethylene layer. The ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer or linear low-density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer or linear low-density polyethylene layer to 1 / 10 or more, the heat resistance of the laminated substrate of the present invention can be improved. Furthermore, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer or linear low-density polyethylene layer to 1 / 1 or less, the processability of the resin film can be improved.
[0028] Polypropylene may be a homopolymer, a random copolymer, or a block copolymer. Polypropylene homopolymer is a polymer consisting solely of propylene; polypropylene random copolymer is a random copolymer of propylene and other α-olefins other than propylene (e.g., ethylene, butene-1, 4-methyl-1-pentene, etc.); and polypropylene block copolymer is a copolymer having polymer blocks made of propylene and polymer blocks made of the aforementioned α-olefins other than propylene. Among these polypropylenes, it is preferable to use homopolymers or random copolymers from the viewpoint of improving the transparency of the polyolefin resin layer and improving the visibility of the image when it is formed on the heat-sealed surface of the polyolefin resin layer. When the rigidity and heat resistance of the laminated substrate are important, homopolymers can be used, and when impact resistance and other factors are important, random copolymers can be used.
[0029] Furthermore, instead of olefin monomers obtained from fossil fuels, biomass-derived olefin monomers may be used as raw materials to obtain polyolefins. Since such biomass-derived olefin monomers are carbon-neutral materials, when the laminated substrate of the present invention is used as the substrate for a laminate for packaging materials and packaging materials are produced, the packaging materials can be made with less environmental impact. Such biomass-derived polyolefins, such as polyethylene, can be produced by methods described in Japanese Patent Publication No. 2013-177531. Alternatively, commercially available biomass-derived polyolefins (for example, GreenPE, commercially available from Braschem) may be used.
[0030] In addition, recycled polyolefins obtained through mechanical recycling can also be used. Mechanical recycling generally involves crushing collected polyolefin films, washing them with alkali to remove dirt and foreign matter from the film surface, and then drying them under high temperature and reduced pressure for a certain period of time to disperse contaminants remaining inside the film, thereby decontaminating the polyolefin film and returning it to its original polyolefin state.
[0031] To provide the polyolefin resin layer with the strength and heat resistance required for packaging, a stretched resin film made of polyolefin is used. The stretched resin film may be either a uniaxially oriented resin film or a biaxially oriented resin film.
[0032] The stretching ratio in the longitudinal direction (MD) of the stretched resin film is preferably 2 times or more and 10 times or less, and preferably 3 times or more and 7 times or less. By setting the stretching ratio in the longitudinal direction (MD) of the stretched resin film to 2 times or more, the strength and heat resistance of the laminated substrate of the present invention can be improved. Furthermore, the transparency of the polyolefin resin layer can be improved, thereby improving the visibility from the back surface when an image is formed on the surface of the polyolefin resin layer. On the other hand, there is no particular upper limit to the stretching ratio in the longitudinal direction (MD) of the stretched resin film, but from the viewpoint of the breaking limit of the stretched film, it is preferable to set it to 10 times or less.
[0033] Furthermore, the stretching ratio in the transverse direction (TD) of the stretched resin film is preferably 2 times or more and 10 times or less, and preferably 3 times or more and 7 times or less. By increasing the stretching ratio in the transverse direction (TD) of the stretched resin film to 2 times or more, the strength and heat resistance of the laminated substrate of the present invention can be improved. Furthermore, the transparency of the polyolefin resin layer can be improved, thereby improving the visibility from the back surface when an image is formed on the surface of the polyolefin resin layer. On the other hand, there is no particular upper limit to the stretching ratio in the transverse direction (TD) of the stretched resin film, but from the viewpoint of the breaking limit of the stretched film, it is preferable to set it to 10 times or less.
[0034] The polyolefin resin layer may have an image formed on its surface. The image formed is not particularly limited and may represent letters, patterns, symbols, or combinations thereof. Image formation can be performed using conventionally known inks, but from the viewpoint of environmental impact, it is preferable to use biomass-derived inks. The method of image formation is not particularly limited and can include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing. Among these, flexographic printing is preferred from the viewpoint of environmental impact.
[0035] Furthermore, it is preferable that the polyolefin resin layer be surface-treated. This improves adhesion with adjacent layers. The surface treatment method is not particularly limited and includes, for example, physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, glow discharge treatment, and chemical treatments such as oxidation treatment using chemicals. Alternatively, an anchor coat layer may be formed on the surface of the polyolefin resin layer using a conventionally known anchor coat agent.
[0036] The thickness of the polyolefin resin layer is preferably 5 μm to 300 μm, and more preferably 7 μm to 100 μm. By making the thickness of the polyolefin resin layer 5 μm or more, the strength of the laminated substrate of the present invention can be improved. Furthermore, by making the thickness of the polyolefin resin layer 300 μm or less, when the laminated substrate of the present invention is used as a base material for a laminated packaging material, the processability of the laminated packaging material can be improved.
[0037] A polyolefin resin layer can be produced by forming a polyolefin film using a T-die method or inflation method, creating a resin film, and then stretching it. The inflation method allows for simultaneous film formation and stretching.
[0038] When producing a polyolefin resin layer by the T-die method, the polyolefin MFR is preferably 5 g / 10 min or more and 20 g / 10 min or less. By setting the polyolefin MFR to 5g / 10min or more, the processability of the laminated substrate of the present invention can be improved. Furthermore, by setting the polyolefin MFR to 20g / 10min or less, it is possible to prevent the resin film from rupturing.
[0039] When producing a polyolefin resin layer by the inflation method, the MFR of the polyolefin is preferably 0.5 g / 10 min or more and 5 g / 10 min or less. By setting the polyolefin MFR to 0.5 g / 10 min or more, the processability of the laminated substrate of the present invention can be improved. Furthermore, by setting the polyolefin MFR to 5 g / 10 min or less, the film-forming properties can be improved.
[0040] Furthermore, the polyolefin resin layer is not limited to those produced by the above method; commercially available ones may also be used.
[0041] (Barrier coat layer) The substrate is provided with a barrier coating layer on the surface of its polyolefin resin layer, thereby improving the barrier properties of the laminated substrate of the present invention, specifically its oxygen barrier properties and water vapor barrier properties.
[0042] In one embodiment, the barrier coat layer includes ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamides such as nylon 6, nylon 6,6 and polymethoxyylene adipamide (MXD6), polyester, polyurethane, and gas barrier resins such as (meth)acrylic resin.
[0043] The gas barrier resin content in the barrier coat layer is preferably 50% by mass or more and 95% by mass or less, and more preferably 75% by mass or more and 90% by mass or less. By setting the gas barrier resin content in the barrier coat layer to 50% by mass or more, the oxygen barrier and water vapor barrier properties of the laminated substrate of the present invention can be further improved.
[0044] The barrier coat layer may contain additives to the extent that they do not impair the properties of the present invention. Examples of additives include crosslinking agents, antioxidants, antiblocking agents, lubricants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, compatibilizers, and pigments.
[0045] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By setting the thickness of the barrier coat layer to 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminated base material of the present invention can be further improved. By setting the thickness of the barrier coat layer to 10 μm or less, the recyclability of the laminate for packaging materials when the laminated base material of the present invention is used as the base material of the laminate for packaging materials can be improved.
[0046] The barrier coat layer can be formed by dissolving or dispersing the above material in water or a suitable solvent, applying the resulting solution or dispersion onto the polyolefin resin layer, and then drying the applied layer. Alternatively, the barrier coat layer can also be formed by applying a commercially available barrier coating agent onto the polyolefin resin layer and drying the applied layer.
[0047] In another embodiment, the barrier coat layer is a gas barrier coating film containing at least one resin composition such as a hydrolyzate of a metal alkoxide or a hydrolysis-condensation product of a metal alkoxide, which is obtained by subjecting a mixture of a metal alkoxide and a water-soluble polymer to polycondensation via a sol-gel method in the presence of a sol-gel method catalyst, water, an organic solvent, and the like. When the laminated base material of the present invention is used as the base material of a laminate for packaging materials, by providing an inorganic oxide vapor-deposited film so as to be adjacent to the barrier coat layer of this form, the occurrence of cracks in the vapor-deposited film can be effectively prevented.
[0048] In one embodiment, the metal alkoxide is represented by the following general formula. R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represent an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the valence of M.)
[0049] As the metal atom M, for example, silicon, zirconium, titanium, aluminum and the like can be used. In addition, R1 and R 2 Examples of organic groups represented by include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, and i-butyl groups.
[0050] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (mass%) Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).
[0051] Furthermore, it is preferable to use a silane coupling agent together with the above-mentioned metal alkoxide. As silane coupling agents, known organic reactive group-containing organoalkoxysilanes can be used, but organoalkoxysilanes having an epoxy group are particularly preferred. Examples of organoalkoxysilanes having an epoxy group include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0052] Two or more of the above-mentioned silane coupling agents may be used, and it is preferable to use the silane coupling agent in an amount of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the above-mentioned alkoxides.
[0053] As water-soluble polymers, polyvinyl alcohol and ethylene-vinyl alcohol copolymers are preferred, and from the viewpoint of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferable to use these in combination.
[0054] The content of the water-soluble polymer in the gas barrier coating film is preferably 5 parts by mass or more and 500 parts by mass or less per 100 parts by mass of metal alkoxide. By setting the content of the water-soluble polymer in the gas barrier coating film to 5 parts by mass or more per 100 parts by mass of metal alkoxide, the oxygen barrier and water vapor barrier properties of the laminated substrate of the present invention can be further improved. Furthermore, by setting the content of the water-soluble polymer in the gas barrier coating film to 500 parts by mass or less per 100 parts by mass of metal alkoxide, the film-forming properties of the gas barrier coating film can be improved.
[0055] The thickness of the gas barrier coating film is preferably 0.01 μm to 100 μm, and more preferably 0.1 μm to 50 μm. This allows for further improvement of oxygen barrier properties and water vapor barrier properties. By setting the thickness of the gas barrier coating film to 0.01 μm or more, the oxygen barrier and water vapor barrier properties of the laminated substrate of the present invention can be improved. Furthermore, in laminated packaging materials, when provided adjacent to an inorganic oxide vapor-deposited film, the occurrence of cracks in the vapor-deposited film can be prevented.
[0056] A gas barrier coating film can be formed by applying a composition containing the above-mentioned materials onto a polyolefin resin layer using conventionally known methods such as roll coating (including gravure roll coaters), spray coating, spin coating, dipping, brushing, barcoding, or applicators, and then polycondensing the composition by a sol-gel method. Suitable catalysts for the sol-gel process include acids or amine compounds. Suitable amine compounds include tertiary amines that are substantially insoluble in water and soluble in organic solvents, such as N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferred. The sol-gel catalyst is preferably used in an amount of 0.01 parts by mass or more and 1.0 part by mass or less per 100 parts by mass of metal alkoxide, and more preferably in an amount of 0.03 parts by mass or more and 0.3 parts by mass or less. The catalytic effect of the sol-gel method catalyst can be improved by using 0.01 parts by mass or more per 100 parts by mass of metal alkoxide. Furthermore, by using 1.0 part by mass or less per 100 parts by mass of metal alkoxide, the thickness of the formed gas barrier coating film can be made uniform.
[0057] The above composition may further contain an acid. The acid is used as a catalyst for the sol-gel process, mainly as a catalyst for the hydrolysis of alkoxides and silane coupling agents. As acids, mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid, as well as organic acids such as acetic acid and tartaric acid, can be used. The amount of acid used is preferably 0.001 moles or more and 0.05 moles or less relative to the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. By using an amount of acid equal to 0.001 moles or more relative to the total molar amount of the alkoxide component (e.g., silicate portion) of the alkoxide and silane coupling agent, the catalytic effect can be improved. Furthermore, by using an amount of acid equal to 0.05 moles or less relative to the total molar amount of the alkoxide component (e.g., silicate portion) of the alkoxide and silane coupling agent, the thickness of the formed gas barrier coating film can be made uniform.
[0058] Furthermore, the above composition preferably contains water in an amount of 0.1 moles to 100 moles, more preferably 0.8 moles to 2 moles, per mole of the total molar amount of alkoxide. By setting the water content to 0.1 moles or more per mole of total alkoxide, the oxygen barrier and water vapor barrier properties of the laminated substrate of the present invention can be improved. Furthermore, by setting the water content to 100 moles or more per mole of total alkoxide, the hydrolysis reaction can be carried out rapidly.
[0059] Furthermore, the above composition may contain an organic solvent. Examples of organic solvents include methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and n-butanol.
[0060] The following describes one embodiment of a method for forming a gas barrier coating film. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and, if necessary, a silane coupling agent. A polycondensation reaction gradually proceeds within this composition. Next, the composition is applied to the polyolefin resin layer and dried using the conventionally known method described above. This drying further promotes the polycondensation reaction between the alkoxide and the water-soluble polymer (and the silane coupling agent if the composition contains one), forming a composite polymer layer. Finally, a gas barrier coating film can be formed by heating the composition at a temperature of 20 to 250°C, preferably 50 to 220°C, for 1 second to 10 minutes.
[0061] The barrier coat layer may have an image formed on its surface. The method for forming the image is as described above.
[0062] (Laminate for packaging materials) As shown in Figure 2, the laminated packaging material 13 of the present invention comprises the laminated base material 10 and the heat seal layer 14. Furthermore, in the present invention, the heat seal layer is made of polyolefin, and the polyolefin constituting the polyolefin resin layer of the laminated substrate and the polyolefin constituting the heat seal layer are the same polyolefin. By adopting such a configuration, the recyclability of the laminate for packaging materials can be improved.
[0063] Furthermore, in one embodiment, as shown in Figure 3, the laminate 13 for packaging materials of the present invention may include a vapor-deposited film 15 between the laminate base material 10 and the heat seal layer 14.
[0064] Furthermore, in one embodiment, as shown in Figure 4, the laminate 13 for packaging materials of the present invention may include an adhesive layer 16 between the laminate substrate 10 and the vapor-deposited film 15.
[0065] Furthermore, in one embodiment, as shown in Figure 5, the heat seal layer 14 in the laminate 10 for packaging material of the present invention may include a first heat seal layer 17 and a second heat seal layer 18.
[0066] The content of the same polyolefin in the entire laminate for packaging materials of the present invention is preferably 80% by mass or more, and more preferably 90% by mass or more. By ensuring that the content of the same polyolefin in the entire laminate for packaging materials of the present invention is 80% by mass or more, the recyclability of the laminate for packaging materials of the present invention can be improved. Furthermore, the content of the same polyolefin in a laminate for packaging materials refers to the ratio of the content of the same polyolefin to the sum of the resin material content in each layer constituting the laminate.
[0067] The following describes each layer that constitutes the laminate for packaging materials of the present invention.
[0068] (Laminated base material) In a laminate for packaging materials, the laminated substrate is provided such that the polyolefin resin layer is the outermost surface. Details of the laminated substrate's composition have been described above and are therefore omitted here.
[0069] (Heat seal layer) The heat-seal layer is characterized by being made of the same polyolefin as the polyolefin resin layer that constitutes the polyolefin resin layer of the laminated substrate described above. By adopting this configuration, it is possible to create a recyclable packaging material while maintaining the strength and heat resistance required for packaging. However, the heat-seal layer is formed from an unstretched polyolefin resin film or from a polyolefin by melt extrusion.
[0070] Furthermore, when polypropylene is used as the heat seal layer, a heat seal modifier may be included to improve heat sealability. The heat seal modifier is not particularly limited as long as it has good compatibility with the polyolefin constituting the heat seal layer, but examples include olefin copolymers.
[0071] The thickness of the heat seal layer is preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm. By making the heat seal layer thickness 5 μm or more, the heat sealability and recyclability of the heat seal layer can be improved. Furthermore, by making the heat seal layer thickness 100 μm or less, the processability of the laminate for packaging material of the present invention can be improved.
[0072] In one embodiment, the heat seal layer may have a multilayer structure. In particular, when a heat seal modifier is added to polypropylene as the heat seal layer, the modifier may migrate (leach out) to the laminated substrate side. Therefore, the heat seal layer can be made up of two or more layers, with the heat-sealed side (the innermost layer of the laminate) being a layer containing polyolefin resin and a heat seal modifier, and the outer layer being a polypropylene layer. Specifically, the multilayer structure includes a first heat-seal layer made of polyolefin and a second heat-seal layer made of polyolefin and a heat-seal modifier.
[0073] The content of the heat seal modifier in the second heat seal layer is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 40% by mass or less. By setting the heat seal modifier content in the second heat seal layer to 10% by mass or more, the heat sealability of the second heat seal layer can be improved. Furthermore, by setting the heat seal modifier content in the second heat seal layer to 50% by mass or less, the recyclability of the laminate for packaging materials of the present invention can be improved.
[0074] Furthermore, when the heat seal layer has the above-described two-layer structure, the thickness of the first heat seal layer is preferably 5 μm or more and 50 μm or less, and more preferably 7 μm or more and 45 μm or less. By setting the thickness of the first heat seal layer to 5 μm or more, the recyclability of the laminate for packaging materials of the present invention and the heat sealability of the first heat seal layer can be improved. Furthermore, by setting the thickness of the first heat seal layer to 50 μm or less, the processability of the laminate for packaging materials of the present invention can be improved. Furthermore, the thickness of the second heat seal layer is preferably 5 μm or more and 20 μm or less, and more preferably 7 μm or more and 15 μm or less. By making the thickness of the second heat seal layer 5 μm or more, the heat sealability of the second heat seal layer can be improved. Furthermore, by making the thickness of the second heat seal layer 20 μm or less, it is possible to achieve both the recyclability and processability of the laminate for packaging material of the present invention.
[0075] (Vaporized film) The laminate for packaging materials of the present invention may further include a vapor-deposited film between the substrate and the heat-seal layer. By including the vapor-deposited film, the oxygen barrier properties and water vapor barrier properties can be further improved.
[0076] Examples of vapor-deposited films include those composed of metals such as aluminum, as well as inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide.
[0077] Furthermore, the thickness of the deposited film is preferably 1 nm to 150 nm, more preferably 5 nm to 60 nm, and even more preferably 10 nm to 40 nm. By setting the thickness of the vapor-deposited film to 1 nm or more, the oxygen barrier and water vapor barrier properties of the laminate for packaging materials of the present invention can be further improved. Furthermore, by setting the thickness of the vapor-deposited film to 150 nm or less, the occurrence of cracks in the vapor-deposited film can be prevented, and the recyclability of the laminate for packaging materials of the present invention can be improved.
[0078] For the vapor-deposited film to be an aluminum vapor-deposited film, its OD value is preferably between 2 and 3.5. This allows for improved oxygen barrier and water vapor barrier properties while maintaining the productivity of the laminate for packaging materials of the present invention. In this invention, the OD value can be measured in accordance with JIS-K-7361.
[0079] Deposited films can be formed using conventionally known methods, such as physical vapor deposition (PVD) methods including vacuum deposition, sputtering, and ion plating, and chemical vapor deposition (CVD) methods including plasma chemical vapor deposition, thermochemical vapor deposition, and photochemical vapor deposition.
[0080] Furthermore, for example, a composite film consisting of two or more deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition methods. The vacuum level of the deposition chamber before oxygen introduction is 10 -2 ~10 -8 A bar of approximately mbar is preferred, and after oxygen introduction, 10 -1 ~10 -6A pressure of approximately mbar is preferred. The amount of oxygen introduced will vary depending on the size of the deposition machine. Inert gases such as argon, helium, or nitrogen may be used as carrier gases for the oxygen introduced, within reasonable limits. The film transport speed can be approximately 10 to 800 m / min.
[0081] It is preferable that the surface of the deposited film is subjected to the above-mentioned surface treatment. This improves adhesion with adjacent layers.
[0082] (adhesive layer) The laminate for packaging materials of the present invention may be provided with an adhesive layer to improve the adhesion between the surface on which the vapor-deposited film is applied and the surface to which the vapor-deposited film adheres (the adherend surface). That is, if a vapor-deposited film is applied to the surface of the heat-seal layer, an adhesive layer can be provided between the vapor-deposited film and the substrate (barrier coat layer).
[0083] The adhesive layer contains at least one type of adhesive, which may be a one-component curing type, a two-component curing type, or a non-curing type. The adhesive may be a solvent-free type or a solvent-based type, but from the viewpoint of environmental impact, a solvent-free type adhesive is preferably used. Examples of solvent-free adhesives include polyether-based adhesives, polyester-based adhesives, silicone-based adhesives, epoxy-based adhesives, and urethane-based adhesives. Among these, two-component curing type urethane-based adhesives are preferably used. Examples of solvent-based adhesives include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.
[0084] Furthermore, when the vapor-deposited film is an aluminum vapor-deposited film, it is preferable that the adhesive layer be composed of a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphate-modified compound. By configuring the adhesive layer in this way, the oxygen barrier and water vapor barrier properties of the laminate for packaging materials of the present invention can be further improved. Furthermore, when forming a laminate with a vapor-deposited film into a packaging material, bending loads are applied to the laminate by the molding machine, which may cause cracks in the aluminum vapor-deposited film. By using the above-described configuration and adhesive layer, even if cracks occur in the aluminum vapor-deposited film, the decrease in oxygen barrier properties and water vapor barrier properties can be suppressed (hereinafter referred to as bending load resistance, depending on the case).
[0085] Polyester polyols have two or more hydroxyl groups as functional groups in one molecule. Isocyanate compounds, on the other hand, have two or more isocyanate groups as functional groups in one molecule. Polyester polyols have, for example, a polyester structure or a polyester polyurethane structure as their main backbone.
[0086] A specific example of a resin composition (adhesive) containing polyester polyol, isocyanate compound, and phosphate-modified compound is the PASLIM series sold by DIC Corporation.
[0087] The resin composition may further contain plate-like inorganic compounds, coupling agents, cyclodextrins and / or their derivatives.
[0088] Examples of polyester polyols having two or more hydroxyl groups in one molecule as functional groups include the following [Example 1] to [Example 3]. [Example 1] Polyester polyol obtained by polycondensation of an ortho-oriented polycarboxylic acid or its anhydride with a polyhydric alcohol [Example 2] Polyester polyol having a glycerol skeleton [Example 3] Polyester polyol having an isocyanuric ring The following describes each type of polyester polyol.
[0089] The polyester polyol of the first example is a polycondensate obtained by polycondensing a polycarboxylic acid component containing at least one orthophthalic acid and its anhydride with a polyhydric alcohol component containing at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. In particular, polyester polyols in which orthophthalic acid and its anhydride are present in a proportion of 70 to 100% by mass relative to the total polycarboxylic acid components are preferred.
[0090] The polyester polyol according to the first example requires orthophthalic acid and its anhydride as polycarboxylic acid components, but other polycarboxylic acid components may be copolymerized to the extent that the effects of this embodiment are not impaired. Specifically, examples include aliphatic polycarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid; unsaturated bond-containing polycarboxylic acids such as maleic anhydride, maleic acid, and fumaric acid; alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids; and polybasic acids such as p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Among these, succinic acid, 1,3-cyclopentanedicarboxylic acid, and isophthalic acid are preferred. Furthermore, two or more of the above-mentioned polycarboxylic acids may be used.
[0091] As an example of a polyester polyol related to the second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In general formula (1), R1, R2, and R3 are each independently either H (hydrogen atom) or a group represented by the following general formula (2). [ka]
[0092] In formula (2), n represents an integer from 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have substituents, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 represents a group represented by general formula (2).
[0093] In general formula (1), at least one of R1, R2, and R3 must be a group represented by general formula (2). In particular, it is preferable that all of R1, R2, and R3 are groups represented by general formula (2).
[0094] Furthermore, the compound may be a mixture of two or more compounds in which one of R1, R2, or R3 is a group represented by general formula (2), two of R1, R2, or R3 are groups represented by general formula (2), or all of R1, R2, and R3 are groups represented by general formula (2).
[0095] X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have substituents. If X is substituted by a substituent, it may be substituted by one or more substituents, the substituents being bonded to any carbon atom on X that is different from the free radical. Examples of substituents include chloro, bromo, methyl, ethyl, i-propyl, hydroxyl, methoxy, ethoxy, phenoxy, methylthio, phenylthio, cyano, nitro, amino, phthalimide, carboxyl, carbamoyl, N-ethylcarbamoyl, phenyl, and naphthyl groups.
[0096] In general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, propylene group, butylene group, neopentylene group, 1,5-pentylene group, 3-methyl-1,5-pentylene group, 1,6-hexylene group, methylpentylene group, and dimethylbutylene group. Among these, propylene and ethylene groups are preferred, with ethylene being the most preferred.
[0097] Polyester resin compounds having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol with an aromatic polycarboxylic acid or its anhydride in which the carboxylic acid is substituted in the ortho position, and a polyhydric alcohol component as essential components.
[0098] Examples of aromatic polycarboxylic acids or their anhydrides in which the carboxylic acid is substituted at the ortho position include orthophthalic acid or its anhydride, naphthalene 2,3-dicarboxylic acid or its anhydride, naphthalene 1,2-dicarboxylic acid or its anhydride, anthraquinone 2,3-dicarboxylic acid or its anhydride, and 2,3-anthracenecarboxylic acid or its anhydride. These compounds may have substituents on any carbon atom of the aromatic ring. Examples of substituents include chloro, bromo, methyl, ethyl, i-propyl, hydroxyl, methoxy, ethoxy, phenoxy, methylthio, phenylthio, cyano, nitro, amino, phthalimide, carboxyl, carbamoyl, N-ethylcarbamoyl, phenyl, and naphthyl groups.
[0099] Furthermore, examples of polyhydric alcohol components include alkylenediols having 2 to 6 carbon atoms. Examples of diols include ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.
[0100] The polyester polyol in the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In general formula (3), R1, R2, and R3 each independently represent either "-(CH2)n1-OH (where n1 is an integer from 2 to 4)" or the structure of general formula (4). [ka]
[0101] In general formula (4), n2 represents an integer from 2 to 4, n3 represents an integer from 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene, 1,2-naphthylene, 2,3-naphthylene, 2,3-anthraquinonediyl, and 2,3-anthracenediyl groups, which may have substituents, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 is a group represented by general formula (4).
[0102] In general formula (3), the alkylene group represented by -(CH2)n1- may be linear or branched. n1 is preferably 2 or 3, with 2 being the most preferred.
[0103] In general formula (4), n² represents an integer between 2 and 4, and n³ represents an integer between 1 and 5. X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have substituents.
[0104] If X is substituted by a substituent, it may be substituted by one or more substituents, the substituents being bonded to any carbon atom on X that is different from the free radical. Examples of substituents include chloro, bromo, methyl, ethyl, i-propyl, hydroxyl, methoxy, ethoxy, phenoxy, methylthio, phenylthio, cyano, nitro, amino, phthalimide, carboxyl, carbamoyl, N-ethylcarbamoyl, phenyl, and naphthyl groups. The substituents of X are preferably hydroxyl, cyano, nitro, amino, phthalimide, carbamoyl, N-ethylcarbamoyl, and phenyl groups, with hydroxyl, phenoxy, cyano, nitro, phthalimide, and phenyl groups being the most preferred.
[0105] In general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, propylene group, butylene group, neopentylene group, 1,5-pentylene group, 3-methyl-1,5-pentylene group, 1,6-hexylene group, methylpentylene group, and dimethylbutylene group. Among these, propylene and ethylene groups are preferred, with ethylene being the most preferred.
[0106] In general formula (3), at least one of R1, R2, and R3 is a group represented by general formula (4). In particular, it is preferable that all of R1, R2, and R3 are groups represented by general formula (4).
[0107] Furthermore, the compound may be a mixture of two or more compounds in which one of R1, R2, or R3 is a group represented by general formula (4), two of R1, R2, or R3 are groups represented by general formula (4), or all of R1, R2, and R3 are groups represented by general formula (4).
[0108] Polyester polyols having an isocyanuric ring, represented by general formula (3), can be synthesized by reacting a triol having an isocyanuric ring with an aromatic polycarboxylic acid or its anhydride in which the carboxylic acid is substituted in the ortho position, and a polyhydric alcohol component as essential components.
[0109] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acids such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.
[0110] Furthermore, examples of aromatic polycarboxylic acids or their anhydrides in which the carboxylic acid is substituted at the ortho position include orthophthalic acid or its anhydride, naphthalene 2,3-dicarboxylic acid or its anhydride, naphthalene 1,2-dicarboxylic acid or its anhydride, anthraquinone 2,3-dicarboxylic acid or its anhydride, and 2,3-anthracenecarboxylic acid or its anhydride. These compounds may have substituents on any carbon atom of the aromatic ring.
[0111] Examples of substituents include chloro group, bromo group, methyl group, ethyl group, i-propyl group, hydroxyl group, methoxy group, ethoxy group, phenoxy group, methylthio group, phenylthio group, cyano group, nitro group, amino group, phthalimide group, carboxyl group, carbamoyl group, N-ethylcarbamoyl group, phenyl group, and naphthyl group.
[0112] Furthermore, examples of polyhydric alcohol components include alkylenediols having 2 to 6 carbon atoms. Examples include ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol. In particular, polyester polyol compounds having an isocyanuric ring are preferred when 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid is used as the triol compound having an isocyanuric ring, an aromatic polycarboxylic acid in which the carboxylic acid is substituted at the ortho position or orthophthalic anhydride is used as the anhydride, and ethylene glycol is used as the polyhydric alcohol, as these compounds exhibit particularly excellent oxygen barrier properties and adhesion.
[0113] The isocyanuric ring is highly polar and trifunctional, which can increase the overall polarity of the system and increase the crosslinking density. From this viewpoint, it is preferable to contain 5% by mass or more of the isocyanuric ring relative to the total solid content of the adhesive resin.
[0114] Isocyanate compounds have two or more isocyanate groups in their molecule. Furthermore, the isocyanate compound may be aromatic or aliphatic, and may be a low-molecular-weight compound or a high-molecular-weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by an addition reaction using a known isocyanate blocking agent by a known and conventional method. In particular, polyisocyanate compounds having three or more isocyanate groups are preferred from the viewpoint of adhesion and retort resistance, and aromatic compounds are preferred from the viewpoint of oxygen barrier properties and water vapor barrier properties.
[0115] Specific examples of isocyanate compounds include, for example, tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, burettes, and allophanates obtained by reacting these isocyanate compounds with low molecular weight active hydrogen compounds or their alkylene oxide adducts, or high molecular weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include high molecular weight active hydrogen compounds of various polyester resins, polyether polyols, and polyamides.
[0116] Phosphate-modified compounds are, for example, compounds represented by the following general formulas (5) or (6). [ka] In general formula (5), R1, R2, and R3 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, an optionally substituted phenyl group, and an alkyl group having 1 to 4 carbon atoms, but at least one of them is a hydrogen atom, and n represents an integer from 1 to 4. [ka] In the formula, R4 and R5 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, an optionally substituted phenyl group, and an alkyl group having 1 to 4 carbon atoms with a (meth)acryloyloxy group, where n is an integer from 1 to 4, x is an integer from 0 to 30, and y is an integer from 0 to 30, except when both x and y are 0.
[0117] More specifically, examples include phosphoric acid, pyrophosphate, triphosphate, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.
[0118] The content of the phosphate-modified compound in the resin composition is preferably 0.005% by mass or more and 10% by mass or less, and more preferably 0.01% by mass or more and 1% by mass or less. By setting the content of the phosphate-modified compound to 0.005% by mass or more, the oxygen barrier and water vapor barrier properties of the laminate for packaging materials of the present invention can be improved. Furthermore, by setting the content of the phosphate-modified compound to 10% by mass or less, the adhesion of the adhesive layer can be improved.
[0119] The resin composition containing polyester polyol, isocyanate compound, and phosphate-modified compound may also contain plate-like inorganic compound, which can improve the adhesion of the adhesive layer. Furthermore, it can improve the bending load resistance of the laminate for packaging materials of the present invention. Examples of plate-like inorganic compounds include kaolinite-serpentine clay minerals (haloysite, kaolinite, endelite, dickite, nacrite, antigorite, chrysotile, etc.) and pyrophyllite-talc group minerals (pyrophyllite, talc, kerolite, etc.).
[0120] Examples of coupling agents include silane-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents represented by the general formula (7) below. These coupling agents may be used individually or in combination of two or more types. [ka]
[0121] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β( Examples include aminoethyl)γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, 3-isocyanatetopropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, and 3-triethoxysilyl-N-(1,3-dimethylbutylidene).
[0122] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate) oxyacetate titanate, bis(dioctyl pyrophosphate) ethylene titanate, isopropyl trioctainol titanate, isopropyl dimethacrylate isostearoyl titanate, isopropyl isostearoyl diacrylic titanate, diisostearoylethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumylphenyl titanate, and dicumylphenyl oxyacetate titanate.
[0123] Specific examples of aluminum-based coupling agents include, for example, acetalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetacetate mono(dioctyl phosphate), aluminum-2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetacetate aluminum oxide trimer.
[0124] The resin composition may contain cyclodextrin and / or its derivatives, thereby improving the adhesion of the adhesive layer. Furthermore, it can further improve the bending load resistance of the laminate for packaging materials of the present invention. Specifically, for example, cyclodextrins such as alkylated cyclodextrins, acetylated cyclodextrins, and hydroxyalkylated cyclodextrins, in which the hydrogen atom of the hydroxyl group of the glucose unit of a cyclodextrin is substituted with another functional group, can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrins and cyclodextrin derivatives may be any of the following: α-cyclodextrin consisting of 6 glucose units, β-cyclodextrin consisting of 7 glucose units, or γ-cyclodextrin consisting of 8 glucose units. These compounds may be used individually or in combination of two or more. Furthermore, these cyclodextrins and / or their derivatives may collectively be referred to as dextrin compounds from now on.
[0125] From the viewpoint of compatibility and dispersibility with resin compositions, it is preferable to use cyclodextrin derivatives as the cyclodextrin compound.
[0126] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin. These compounds may be used individually or in combination of two or more.
[0127] Examples of acetylated cyclodextrins include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, and monoacetyl-γ-cyclodextrin. These compounds may be used individually or in combination of two or more.
[0128] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin. These compounds may be used individually or in combination of two or more.
[0129] The thickness of the adhesive layer is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1 μm or more and 4.5 μm or less. By making the adhesive layer thickness 0.5 μm or more, the adhesive properties of the adhesive layer can be improved. Furthermore, if the adhesive layer is composed of a cured product of a resin composition containing polyester polyol, isocyanate compound, and phosphate-modified compound, the bending load resistance of the laminate for packaging materials can be improved. By reducing the thickness of the adhesive layer to 6 μm or less, the processability of the laminate for packaging materials can be improved.
[0130] The adhesive layer can be formed by applying and drying it on a substrate or the like using conventionally known methods such as the direct gravure roll coating method, gravure roll coating method, kiss coating method, reverse roll coating method, fontein method, and transfer roll coating method.
[0131] (packaging material) The packaging material of the present invention is characterized by being composed of the above-mentioned laminate for packaging materials. The shape of the packaging material is not particularly limited, and may be in the shape of a bag, as shown in Figure 6. In one embodiment, a bag-shaped packaging material can be manufactured by folding the laminate of the present invention in half and overlapping the two layers so that the heat-seal layer faces inward, and then heat-sealing the edges. In another embodiment, the bag-shaped packaging material can also be manufactured by overlapping two laminates so that their heat-seal layers face each other, and then heat-sealing the edges. In the diagram, the shaded areas represent the heat-sealed portions.
[0132] The heat sealing method is not particularly limited and can be carried out by known methods such as bar seals, rotary roll seals, belt seals, impulse seals, high-frequency seals, and ultrasonic seals.
[0133] In one embodiment, the packaging material has a stand-up pouch shape with a body and a bottom, as shown in Figure 7. A stand-up pouch-type packaging material can be manufactured by first forming a body by heat-sealing the laminated packaging material in a cylindrical shape with the heat-seal layer facing inward, and then folding another laminated packaging material in a V-shape with the heat-seal layer facing inward, sandwiching it from one end of the body, and heat-sealing it to form the bottom.
[0134] The contents to be filled into the packaging material are not particularly limited and may be liquids, powders, or gels. They may also be food products or non-food products. After filling with contents, the opening can be heat-sealed to create a package. [Examples]
[0135] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0136] Example 1 A biaxially oriented polypropylene film (manufactured by Toyobo Co., Ltd., product name: P2108) with a thickness of 18 μm was prepared as the polyolefin resin layer. A polyvinyl alcohol-based barrier coating agent (manufactured by Michelman Co., Ltd., EKF1407.F) was applied to one side of this film by gravure printing and dried to form a 1 μm thick barrier coating layer, thereby creating a laminated substrate.
[0137] An image was formed on the barrier coat layer created as described above using a solvent-based gravure ink (Finato, manufactured by DIC Graphics Co., Ltd.) by gravure printing.
[0138] As the heat seal layer, polypropylene (manufactured by TPC Corporation, product name: FL7540L, density: 0.90 g / cm³) is used. 3 An unstretched polypropylene film with a thickness of 35 μm was prepared by extrusion using a T-die method with a melting point of 138°C and a melting rate of 7.0 g / 10 min.
[0139] A 30 nm thick aluminum vapor-deposited film was formed on one side of the unstretched polypropylene film prepared as described above, using the PVD method. The vapor deposition concentration (OD value) of the formed film was measured to be 3.0.
[0140] A laminate for packaging material was obtained by laminating the barrier coat layer surface of a laminated substrate and the vapor-deposited film-forming surface of a heat-seal layer via a two-component curing polyurethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-3600 / H-689). The proportion of identical polyolefin (PP) in the laminate for packaging material obtained in this way was 93% by mass.
[0141] Example 2 A laminate for packaging materials of the present invention was prepared in the same manner as in Example 1, except that the thickness of the aluminum vapor-deposited film was changed to 20 nm and the OD value of the vapor-deposited film was changed to 2.0. The proportion of the same polyolefin (PP) in the laminate for packaging materials obtained in this manner was 93% by mass.
[0142] Example 3 A laminate for packaging materials of the present invention was prepared in the same manner as in Example 1, except that the two-component curing polyurethane adhesive was replaced with a two-component curing adhesive containing a polyester polyol, an isocyanate compound, and a phosphate-modified compound (manufactured by DIC Corporation, trade name: PASLIM VM001 / VM102CP). The proportion of identical polyolefin (PP) in the laminate for packaging materials obtained in this manner was 93% by mass.
[0143] Comparative Example 1 A laminate for packaging material was obtained in the same manner as in Example 1, except that an unstretched polypropylene film with a thickness of 18 μm (manufactured by Toyobo Co., Ltd., product name: P1108) was used as the polyolefin resin layer. The proportion of identical polyolefin (PP) in the laminate obtained in this manner was 93% by mass.
[0144] Comparative Example 2 A laminate for packaging material was obtained in the same manner as in Example 1, except that the laminated substrate was configured without a barrier coat layer. The proportion of the same polyolefin (PP) in the laminate obtained in this way was 95% by mass.
[0145] Comparative Example 3 A laminate for packaging material was obtained in the same manner as in Example 1, except that the base material was a 12 μm thick biaxially oriented polyester film (manufactured by Toyobo Co., Ltd., product name: E5100). The proportion of the same polyolefin (PP) in the laminate obtained in this manner was 69% by mass.
[0146] <<Recyclability Assessment>> The recyclability of the laminates for packaging materials obtained in the above examples and comparative examples was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ○: The content of the same polyolefin in the laminate for packaging materials was 80% by mass or more. ×: The content of the same polyolefin in the laminate for packaging materials was less than 80% by mass.
[0147] <<Strength Evaluation>> The laminated packaging materials prepared in the above examples and comparative examples were tested for their strength when punctured with a 0.5 mm diameter needle using a tensile testing machine (Orientec Co., Ltd., product name: RTC-1310A). The puncture speed was set to 50 mm / min. The measurement results are summarized in Table 1.
[0148] <<Heat Resistance Evaluation>> Two test pieces measuring 80 mm in length and 80 mm in width were prepared from the laminated packaging materials obtained in the above examples and comparative examples. Two test pieces were placed on top of each other with their heat-sealed layers facing each other, and three sides were heat-sealed at 150°C to create a small pouch-shaped packaging material. The fabricated packaging materials were visually inspected, and the heat resistance of the laminated packaging material was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ○: No wrinkles or other defects were observed on the surface of the packaging material, and no adhesion to the heat seal bar was observed. ×: Wrinkles and other defects were present on the surface of the packaging material, and it was also found to be adhering to the heat seal bar, making it impossible to form bags.
[0149] <<Oxygen Barrier Assessment>> The laminated packaging material obtained in the above examples and comparative examples was cut to A4 size, and the oxygen permeability (cc / m³) was measured using OXTRAN2 / 20 manufactured by MOCON, Inc., USA, in an environment of 23°C and 90% relative humidity. 2 The / day / atm (atm) was measured. The measurement results are summarized in Table 1.
[0150] <<Evaluation of water vapor barrier properties>> The laminated packaging material obtained in the above examples and comparative examples was cut to A4 size, and the water vapor transmission rate (g / m³) was measured using PERMATRAN3 / 31 manufactured by MOCON, Inc., USA, in an environment of 40°C and 90% relative humidity. 2 The / day / atm (atm) was measured. The measurement results are summarized in Table 1.
[0151] <Bending load resistance evaluation> The laminated packaging material obtained above was subjected to a flex load (stroke: 155 mm, flexing motion: 440°) five times using a Gelboflex teter (manufactured by Tester Industries Co., Ltd., product name: BE1006BE) in accordance with ASTM F 392. After bending, the oxygen and water vapor permeability of the laminated packaging material was measured. The measurement results are summarized in Table 1.
[0152] <<Heat sealability test>> The laminated packaging material obtained in the above examples and comparative examples was cut into 10cm x 10cm pieces to create sample pieces. These sample pieces were folded in half with the heat-seal layer facing inward, and the temperature was set to 140°C and the pressure to 1kgf / cm². 2 A 1cm x 10cm area was heat-sealed under a 1-second condition. The heat-sealed sample pieces were cut into 15mm wide strips, and the unheat-sealed ends were gripped in a tensile testing machine. The peel strength (N / 15mm) was measured under conditions of a speed of 300mm / min and a load range of 50N. The measurement results are summarized in Table 1. In Comparative Example 1, the laminated packaging material obtained adhered to the heat seal bar, making it impossible to measure the peel strength, therefore it was marked as "-".
[0153] [Table 1] [Explanation of Symbols]
[0154] 10: Laminated substrate, 11: Polyolefin resin layer, 12: Barrier coat layer, 13: Laminate for packaging material, 14: Heat seal layer, 15: Vapor-deposited film, 16: Adhesive layer, 17: First heat seal layer, 18: Second heat seal layer
Claims
1. A laminate for packaging material comprising at least a base material and a heat seal layer, wherein a vapor-deposited film is provided between the base material and the heat seal layer, and the vapor-deposited film is provided on the surface of the heat seal layer, The substrate comprises at least a polyethylene resin layer and a barrier coating layer. The polyethylene resin layer and the barrier coating layer are in contact. The barrier coating layer is a gas barrier resin layer comprising at least one gas barrier resin selected from ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyacrylonitrile, polyamide, polyester, polyurethane, and (meth)acrylic resin. The content of the gas barrier resin in the barrier coating layer is 75% by mass or more. The barrier coat layer is an unstretched layer. A laminate for packaging materials, characterized in that the polyethylene resin layer is a stretched layer.
2. The laminate for packaging material according to claim 1, wherein the thickness of the barrier coating layer is less than the thickness of the polyethylene resin layer and is 0.01 μm or more and 10 μm or less.
3. The laminate for packaging material according to claim 1, characterized in that the heat seal layer is made of polyethylene resin.
4. The laminate for packaging material according to claim 3, comprising an adhesive layer between the substrate and the vapor-deposited film.
5. The aforementioned vapor-deposited film is an aluminum vapor-deposited film. The laminate for packaging material according to claim 4, wherein the adhesive layer comprises a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphate-modified compound.
6. The packaging material laminate according to any one of claims 3 to 5, wherein the polyethylene resin content in the entire packaging material laminate is 80% by mass or more.
7. A packaging material comprising a laminate for packaging materials as described in claim 6.
Citation Information
Patent Citations
Barrier film and laminated material using the same
JP2000263722A
Laminate
JP2001191462A
Gas barrier film, packaging material, package
JP2009202519A
Container for packaging food or medical care comprising gas barrier laminate
JP2012158348A
Flexible barrier packaging derived from renewable resources
JP2014515714A